Proceedings of the 11th Annual SIGCSE Conference on Innovation and Technology in Computer Science Education 2006
DOI: 10.1145/1140124.1140162
|View full text |Cite
|
Sign up to set email alerts
|

Mental models of recursion revisited

Abstract: Students struggle to understand recursion and we need to find good ways to teach the concept. We believe that an understanding of the mental models of recursion that students develop will assist us in teaching them more effectively. In 2003 we reported on a study of the mental models our students developed. This paper discusses some changes that we made to our teaching in 2003 after that study. An analysis of the students' mental models in 2003, 2004 and 2005 shows that more students are developing the copie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The step, return value and algebraic models simply demonstrate various forms of confusion on the part of the student. Sanders et al (2006) corroborated the findings of Götschi et al (2003) as regards the first year students. Subsequent work (unpublished) identified the existence of a risky viable passive mental model of recursion where only the passive flow is shown.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…The step, return value and algebraic models simply demonstrate various forms of confusion on the part of the student. Sanders et al (2006) corroborated the findings of Götschi et al (2003) as regards the first year students. Subsequent work (unpublished) identified the existence of a risky viable passive mental model of recursion where only the passive flow is shown.…”
Section: Introductionsupporting
confidence: 83%
“…In addition, the research highlighted the fact that understanding of the process is not related to the demonstrated trace mental model. Previous research has indicated that the supposedly simple tail recursive algorithms should be avoided because these can make students think of recursion as a "loop" (Sanders et al, 2006). This research shows that embedded recursive functions, where there are executable lines of code both before and after the recursive call, should be used as the first examples in teaching the concept.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations